A microfabricated 96‐well wound‐healing assay. Issue 12 (20th November 2017) - Luan, Shaoliang; Hao, Rui; Wei, Yuanchen; Chen, Deyong; Fan, Beiyuan; Dong, Fengliang; Guo, Wei; Wang, Junbo; Chen, Jian
Abstract: This article presents a microfabricated 96‐well wound‐healing assay enabling high‐throughput measurement of cellular migration capabilities. Within each well, the middle area is the wound region, made of microfabricated gold surface with self‐assembled PEG repellent for cell seeding. After the formation of a cellular confluent monolayer around the wound region, collagen solution was applied to form three‐dimensional matrix to cover the PEG surface, initiating the wound‐healing process. By interpreting the numbers of migrated cells into the wound regions as a function of specific stimuli with different concentrations, EC50 (half‐maximal effective concentration) was obtained. Using H1299 as a model, values of EC50 were quantified as 8% and 160 ng/ml for fetal bovine serum and CXCL12, respectively. In addition, the values of EC50 were demonstrated not to be affected by variations in compositions of extracellular matrix and geometries of wounds, which can thus be regarded as an intrinsic marker. Furthermore, the migration capabilities of a second cell type (HeLa) were characterized by the developed wound‐healing assay, producing EC50 of 2% when fetal bovine serum was used as the stimuli. These results validated the proposed high‐throughput wound‐healing assay, which may function as an enabling tool in studying cellular capabilities of migration and invasion. © 2017 International Society for Advancement of Cytometry